Differential sensitivity of ammonia oxidising archaea and bacteria to matric and osmotic potential. (February 2019) - Bello, Marcus O.; Thion, Cécile; Gubry-Rangin, Cécile; Prosser, James I.
Abstract: Microbial oxidation of ammonia controls the rate of nitrification in the majority of soils. Both nitrification rate and the composition of communities of ammonia oxidising archaea (AOA) and ammonia oxidising bacteria (AOB) are influenced by drought, with evidence that AOA are more sensitive to periods of drought than AOB. This has been explained by greater sensitivity of AOA to ammonia concentration, which will increase in soil solution during drought, but an alternative, previously unexplored explanation, is greater sensitivity of AOA to matric and/or osmotic stress. A soil microcosm experiment was designed to distinguish these different explanations in which AOA and AOB abundances ( amoA abundance) and nitrification rate were measured over 28 days in nine treatments corresponding to all combinations of three soil matric potentials and three initial ammonia concentrations. Comparison of amoA abundance dynamics suggested that AOA were more susceptible to reduced matric potential than AOB, irrespective of soil ammonia concentration. The greater sensitivity of soil AOA to osmotic stress was also tested in 10-day cultures of representative strains of AOA and AOB in liquid medium containing different concentrations of NaCl and sorbitol as osmo-inducer. AOA were significantly more sensitive to osmotic stress than AOB. These results provide evidence for greater sensitivity of AOA than AOB to both components of water stress, matric and osmotic potential, representing an additional niche differentiation between these two essential groups of ammonia oxidisers. Highlights: NH3 -oxidising archaea (AOA) more sensitive to drought than NH3 -oxidising bacteria (AOB). Water stress more important than NH3 conc. in explaining effects of drought. Pure culture studies supported greater sensitivity of AOA to water stress. Evidence that desiccation tolerance is niche differentiation factor for AOA and AOB. Findings challenge proposals that NH3 conc. explains AO responses to drought.